Justice for People: Thomas Stamford Raffles, Jury System, and Court of Circuit - Wijaya, Daya Negri (TAWARIKH, 2016)
ABSTRACT: In the early eighteenth century, there were two revolutions changing the socio-cultural pattern of the mankind. Those were the American Revolution in 1776, and the French revolution in 1789. The later revolution had shaped Thomas Stamford Rafflesâ mind that the emerging of the middle-class forced the aristocrats to agree the limitation of power through constitution. Thomas Stamford Raffles was an actor and a product of the late eighteenth century humanitarian movement. His way of thinking was inspired by the French enlightenment. It is believed that justice is difficult to be raised. However, many thinkers seem to argue that the state would guarantee the appearance of justice, but they are failed to see the practice of justice. One of the influenced actors is Thomas Stamford Raffles. He was led by the humanitarian movement of his age. He pursued the spirit and executed it as the official policies. Those policies were revision of Dutch and King of Nusantara (Indonesian archipelago)âs treaties leading to the direct rule system; the practice of land-rent system; and re-organization of administration. This study used library research. This study had used some steps, mainly in reading critically and making a note. It considered all Thomas Stamford Rafflesâ primary sources, which were available in online and offline library. In addition, this study analysed and compared the findings with othersâ findings. This study will focus on the third policy. This tends to elaborate the practice of jury system and the court of circuit.KEY WORDS: Legal History; Justice; Thomas Stamford Raffles; British Colonization; Humanism.About the Author: Daya Negri Wijaya is a Lecturer at the History Department, Faculty of Literature UM (State University of Malang), Jalan Semarang No.5, Malang City, East Java, Indonesia. For academic purposes, the author can be contacted via his e-mails address at: dayawijaya15@yahoo.comÂ andÂ daya.negri.fis@um.ac.idHow to cite this article? Wijaya, Daya Negri. (2016). âJustice for People: Thomas Stamford Raffles, Jury System, and Court of Circuitâ in TAWARIKH: International Journal for Historical Studies, Vol.8(1) October, pp.21-30. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (June 25, 2016); Revised (August 19, 2016); and Published (October 28, 2016).